A vicious or auspicious cycle: The reciprocal relation between harsh parental discipline and children's self-regulation. Issue 3 (4th May 2019) - Baron, Alex; Malmberg, Lars-Erik
Abstract: Children's ability to exercise self-regulation is a key predictor of academic, behavioural, and life outcomes, but the developmental dynamics of children's self-regulation are not adequately understood. We investigated how children's self-regulation skills and harsh parental discipline reciprocally predict each other across 12, 474 children at ages three, five, and seven in the U.K. (Millennium Cohort Study). Cross-lagged structural equation models indicated that high initial levels of harsh parental discipline predicted lower subsequent self-regulation, which then reciprocally predicted higher levels of harsh parental discipline. Conversely, high initial levels of child self-regulation predicted lower subsequent harsh parental discipline. Implications for policy and interventions are discussed.